2003
DOI: 10.1159/000072796
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences and Hormonal Modulation of G Proteins Gα<sub>q/11</sub> Expression in Lymphoid Organs

Abstract: Androgens and estrogens exert potent divergent feedback effects on gonadotropin-releasing hormone (GnRH) production at the level of the hypothalamus and GnRH action at the level of the pituitary. Androgens exert generally suppressive effects on GnRH production and action, whereas rising levels of estradiol increase both GnRH release and action. In addition to its known endocrine actions, GnRH possesses immunomodulatory effects. We have previously demonstrated gender differences in immune responsiveness to GnRH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 22 publications
0
5
1
Order By: Relevance
“…This is in contrast with other studies that found a lower Gnaq expression in RA lymphocytes (Wang et al, 2012). Interestingly, there is also a gender bias as the expression of Gnaq increases in an oestrogen-dependent manner in immune cells (Morton et al, 2003).…”
Section: Discussioncontrasting
confidence: 99%
“…This is in contrast with other studies that found a lower Gnaq expression in RA lymphocytes (Wang et al, 2012). Interestingly, there is also a gender bias as the expression of Gnaq increases in an oestrogen-dependent manner in immune cells (Morton et al, 2003).…”
Section: Discussioncontrasting
confidence: 99%
“…We have observed similar self-priming effects of GnRH in immune cells. We have recently demonstrated that both estrogen and GnRH are able to induce GnRH's primary signal transducers, namely, the homologous G proteins, G␣ q and G␣ 11, in immune cells in mice (17,43). We speculate that GnRH-deficient mice, which are deficient in both estrogen and GnRH, may have a relative insufficiency of these stimulatory G proteins.…”
Section: Discussionmentioning
confidence: 96%
“…This is in contrast with other studies that found a lower GNAQ expression in RA lymphocytes ( Wang et al., 2012 ). Interestingly, there is also a gender bias as the expression of GNAQ increases in an oestrogen-dependent manner in immune cells ( Morton et al., 2003 ). In addition, as outlined above, the metabolic regulation of lymphocytes and macrophages from RA patients is fundamentally different.…”
Section: Discussionmentioning
confidence: 99%